2016
DOI: 10.1186/s40064-016-2423-y
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of soil plugging effect inside sleeve of cast-in-place piles driven by vibratory hammers in clays

Abstract: During driving sleeve of cast-in-place piles by vibratory hammers, soils were squeezed into sleeve and then soil plugging was formed. The physic-mechanical properties of the soil plug have direct influence on the load transmission between the sleeve wall and soil plug. Nevertheless, the researches on this issue are insufficient. In this study, finite element and infinite element coupling model was introduced, through the commercial code ABAQUS, to simulate the full penetration process of the sleeve driven from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Xiao et al 13 used infinite element boundary simulations of infinite soils to study the effect of soil blockage during vibrations of grouted piles. Kouroussis et al 14 calculated the structural response of vehicle loads on roadbeds to study the propagation and reflection effects of infinite element boundaries on load waves.…”
Section: Calculation Modelmentioning
confidence: 99%
“…Xiao et al 13 used infinite element boundary simulations of infinite soils to study the effect of soil blockage during vibrations of grouted piles. Kouroussis et al 14 calculated the structural response of vehicle loads on roadbeds to study the propagation and reflection effects of infinite element boundaries on load waves.…”
Section: Calculation Modelmentioning
confidence: 99%
“…Xiao et al 19 . indicated that the soil reaches a partially plugged during the high‐frequency vibration penetration of the pipe pile, where the soil plug moves upward relative to the sleeve wall.…”
Section: Basic Assumptions and The Establishment Of Equationsmentioning
confidence: 99%
“…proposed the simplified calculation of soil plug resistanceQplug${Q_{plug}}$ Qplug=πdfalse(Hhfalse)Hηp+false(e4ηz/d1false)p+γd4ηdz\begin{equation}{Q_{plug}} = \pi d\int\limits_{(H - h^{\prime})}^H {\eta \left[ {p + ({e^{4\eta z/d}} - 1)\left( {p + \frac{{\gamma ^{\prime}d}}{{4\eta }}} \right)} \right]} dz\end{equation}where H$H$ is the penetration depth, h$h^{\prime}$ is the effective soil plug height, d$d$ is the pipe pile diameter, p$p$ is the boundary pressure, γ$\gamma ^{\prime}$ is the effective soil gravity, and η$\eta $ is a coefficient that depends on the earth pressure coefficientK$K$ and contact friction coefficienttanδ$\tan \delta $. Specific parameter determination methods are based on Xiao et al 19 …”
Section: Basic Assumptions and The Establishment Of Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic vibrations are generated in the surroundings of roads as well as train and tram lines [1][2][3]. These vibrations also occur in the vicinity of construction works [4][5][6][7][8]. From the source of the anthropogenic dynamic load, vibrations are transmitted through the rock mass and the foundation structure of the building to the superstructure.…”
Section: Introductionmentioning
confidence: 99%